Development of Leadership Competence and Self Improvement of the Leaders - Slobodan Ristic; Zoran Cekerevac (Communications - Scientific letters of the University of Zilina, 2012)
To be a good leader one always has to have a vision. He knows what he wants to reach and how to get it. In such competitive environment as it is today, leader must prepare himself to daily new challenges. This article deals with leadership, and especially with leader’s self improvement and development of leadership competence. Introductory part of the article gives one of possible classifications of leader’s skills with a brief explanation of each named skill. There are also given some experiences of some of the most successful world’s companies in the area of the strategic rotating and moving managers to appropriate leader’s positions. In the article, there are also analyzed contemporary trends in development of leadership skills and the five phases of development of leadership development according to the Witten-Cameron model. Under Conclusions, there are summarized results of the analysis.